História local de Manoel Viana: subsídio para professores - Menezes, Kélen Elidiane dos Santos (2023)
This research is linked to the Area of concentration in Architecture and Material Heritage, through the Archeology and Paleontology research line of the Professional Master's Degree in Cultural Heritage at the Federal University of Santa Maria (UFSM), it will discuss the history of Manoel Viana’s formation. The main focus of the study is the territory where the municipality is located. The research begins with studies on archeology, the occupation of the site by native peoples, the European invasions, the delimitation of the territory until its political emancipation. The main objective of this study is to research and organize these documents forming a timeline, which will result in the product of this master's degree, a book that will tell the story of Manoel Viana. The main justification for the development of this product it’s because it is a pioneer in the municipality, and there is neither book nor memorials about the local history of the municipality in the way that will be presented in this product. Another and no less important justification for choosing this product is the difficulty that local school teachers found in seeking support for the development of their pedagogical activities in the territory in which they are inserted, since this theme is evidenced in the National Common Curricular Base (BNCC), in the Referencial Gaúcho and in the Municipal Guidance Document. The applied methodology is qualitative, through research in documents and bibliographies on the topics covered. This research will bear fruit, a compact book, easy to understand, which will be made available in e-book form and in print. It is concluded that archeology and local history are fundamental gears for Heritage Education and the immortalization of heritage. When educators have easy access to information, they will be able to approach in their pedagogical activities topics related to archeology and local history in a meaningful way, making knowledge ascendant and progressive, in which one the students will be able to appropriate and recognize the place where they are inserted, and forming conscious historical individuals of their place within history.